Cu-Al alloy interconnection material and preparation method and application thereof
Nanocrystalline structures were prepared by electroplating Cu-Al alloy interconnect materials, which solved the resistivity and electromigration damage problems of Cu interconnects at the sub-10nm process node. This enabled low-cost and high-efficiency interconnect material preparation, improving the performance and reliability of semiconductor devices.
Patent Information
- Application Number
- CN202510947170.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-09
- Publication Date
- 2025-10-17
AI Technical Summary
At the sub-10nm process node, existing technologies struggle to address the issues of increased resistivity and electromigration damage in Cu interconnects. Furthermore, traditional fabrication processes are costly and require complex equipment, making it difficult to meet the demands for small-size interconnect materials.
A Cu-Al alloy interconnect material preparation method is adopted, in which a copper-aluminum alloy coating is prepared in an aqueous solution system by electroplating, combined with annealing heat treatment to form a nanocrystalline structure. The alloy composition is precisely controlled by pulse electroplating technology, which is adapted to the Damascene process and reduces equipment investment and production costs.
It achieves low resistivity and high electromigration resistance, significantly reducing equipment investment and production costs, is compatible with existing semiconductor production lines, improves interconnect performance and reliability, and is suitable for wafer-level interconnect manufacturing of 28nm and below processes.
Smart Images

Figure CN120797113A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of semiconductor material manufacturing, and in particular to a Cu-Al alloy interconnection material and a preparation method and application thereof. BACKGROUND
[0002] Moor's law refers to the number of transistors on an integrated circuit chip doubling about every 18-24 months. Under the driving of Moor's law, semiconductor device manufacturing processes continue to progress, and the size of transistors and interconnection lines in chips continues to shrink. However, the reduction in the size of the interconnection line also brings a series of problems and challenges: first, due to the size effect of the interconnection line, the resistivity will increase significantly after the size of the interconnection line is reduced, thereby causing a rapid rise in interconnection signal delay; second, the reduction in the size of the interconnection line will lead to an increase in current density, which is prone to electromigration damage. Therefore, it is necessary to develop an interconnection material with reliable stability, electromigration resistance and small resistivity at a small scale.
[0003] At present, in the sub-10nm process node, as the Cu line microshrinkage gradually becomes difficult, it is a consensus to find a new alternative metal. In 2018, the Interuniversity Microelectronics Centre (IMEC) theoretically predicted the metals and alloys that can replace Cu through the first-principle method based on the Fermi surface. IMEC proposed using the product of the bulk resistivity p0 and the average electron free path l as the evaluation standard of the conductive ability of the material in the process of size microshrinkage. Shorter average electron free path makes the trend of resistance rise of the metal in the process of size microshrinkage weaker, so low bulk resistivity and short average free path ensure that the material can still maintain low resistance after size reduction. In addition to the size of p0 x l, cohesive energy is also an excellent indicator for investigating the performance of interconnection materials. The cohesive energy of a metal can represent its electromigration resistance and diffusion resistance performance. Generally, metals with high cohesive energy have higher reliability under high current density and are not easy to diffuse into the dielectric layer. Among metal elements, cobalt, ruthenium, molybdenum and other elements have become potential candidate materials because of their similar or lower p0 x l value and higher cohesive energy than Cu.
[0004] In addition to the metal interconnect material system, in recent years, the industry will look for a suitable interconnect material on the alloy. Binary alloy material atomic arrangement long-range order, low resistivity and stable structure, has a greater possibility of becoming the next generation of advanced interconnection material. Through the size effect performance theory calculation of resistivity, below 10nm, the resistivity of NiAl, CuAl3, RuAl alloy polycrystalline thin film will be lower than Cu. At the same time, the alloy has a strong chemical bond and a large cohesive energy, which is very favorable for high reliability filling. At present, there are a few reports on the preparation and resistivity optimization process of alloy, mainly focusing on NiAl and CuAl2. However, the preparation process of the alloy at present is mainly magnetron sputtering, and the process cost and operation cost of the sputtering equipment are high, which needs special devices such as vacuum and external magnetic field. Compared with magnetron sputtering, the electroplating equipment and process are relatively simple, and the deposition rate is usually higher than that of sputtering, and the production efficiency is higher.
[0005] Therefore, researchers in the field are committed to developing a Cu-Al alloy interconnect material and a preparation method and application thereof. SUMMARY
[0006] In order to achieve the above purpose, the present application provides a preparation method of Cu-Al alloy interconnect material, comprising the following steps:
[0007] Step 1, a certain amount of aluminum salt is dissolved in deionized water and mixed uniformly to obtain an aluminum salt solution;
[0008] Step 2, the electroplating substrate is pretreated, the conductive cathode substrate is pasted with insulating glue, the conductive area is controlled, then the power is turned on to remove oil, and the substrate is treated with dilute sulfuric acid pickling and deionized water washing to obtain a clean conductive substrate after treatment;
[0009] Step 3, the conductive substrate is immersed in the aluminum salt solution, and the aluminum salt solution is activated to obtain an activated plating solution;
[0010] Step 4, copper salt is added to the activated plating solution, and the mixed plating solution containing copper ions and aluminum ions is obtained after sufficient mixing and stirring;
[0011] Step 5, the pretreated conductive cathode substrate and metal anode material are immersed in the mixed plating solution for electroplating to obtain a copper-aluminum alloy plating layer;
[0012] Step 6, after electroplating, the sample is taken out, the copper-aluminum alloy plating layer is quickly rinsed with deionized water and dried, then the insulating glue is removed, and then the whole sample is rinsed with deionized water and dried to obtain a plating layer without surface pollution;
[0013] Step 7, the plating layer obtained in step 6 is subjected to annealing heat treatment to obtain a copper-aluminum alloy.
[0014] Further, the aluminum salt in step 1 includes one or more of aluminum triflate, aluminum bistrifluoromethylsulfonimide, aluminum bisfluorosulfonimide, aluminum trifluoroacetate, and the concentration of the aluminum salt is 0.2-5 M / L.
[0015] Further, the concentration of the dilute sulfuric acid in step 2 is 1.54 mol / L.
[0016] Further, the copper salt in step 4 is copper sulfate pentahydrate, and the concentration of the copper salt is 100-2000 ppm.
[0017] In a preferred embodiment of the present application, in step 5, the electroplating is direct current electroplating, the current density during electroplating is 1-6.25 A / dm 2 , the electroplating time is 3-20 min, and the stirring speed during electroplating is 500-1800 rpm.
[0018] In another preferred embodiment of the present application, in step 5, the electroplating is pulse electroplating, the average current density is 1-6.25 A / dm 2 , the pulse width is 0.2-1 s, the total electroplating time is 3-10 min, and the stirring speed during electroplating is 1000-2000 rpm.
[0019] Further, in step 7, the heating rate of the annealing heat treatment is 5-20 ℃ / min, the temperature of the annealing heat treatment is 250-450 ℃, and the holding time of the annealing heat treatment is 1-3 h.
[0020] The present application also provides a Cu-Al alloy interconnection material prepared according to the above method, and the atomic ratio of Cu to Al in the copper-aluminum alloy coating is 0.1-10:1.
[0021] Further, the copper-aluminum alloy after the annealing heat treatment forms a nanocrystalline structure, and the average grain size is 50-200 nm.
[0022] The present application also provides the application of the Cu-Al alloy interconnection material prepared according to the above preparation method in semiconductor devices.
[0023] Technical effects
[0024] 1. The electrodeposition preparation technology of the present application does not require a vacuum environment and high-energy consumption equipment compared with traditional physical vapor deposition, magnetron sputtering and other methods, the process is simple and easy to control, the material utilization rate is as high as 95% or more, and the equipment investment and production cost are significantly reduced; by optimizing the electrolyte formula and pulse electroplating technology, uniform deposition of a micron-level Cu-Al alloy layer can be realized, and the problems of composition segregation or uneven thickness in traditional processes are avoided;
[0025] 2. The preparation method of the present application can realize precise regulation of components. By adjusting electrolyte Cu 2+ / Al 3+ concentration ratio, current density, pulse plating time, annealing temperature and other parameters, the Al content in the alloy can be accurately controlled, and copper-aluminum alloys with different proportions, such as Al2Cu and Cu9Al4, can be formed, while the electrical conductivity and mechanical strength are considered;
[0026] 3. The electrolyte system in the preparation method of the present application adopts a cyanide-free, low-acid / alkali formula, which meets the environmental friendly standard, and the wastewater treatment cost is low. At the same time, the process is compatible with the existing Damascene plating production line of semiconductor, without the need for large-scale equipment modification, and is convenient for upgrading the traditional Cu interconnection production line;
[0027] 4. The Cu-Al alloy plating layer obtained by the present application can be applied to interconnection lines in the field of integrated circuit interconnection, and has the potential to improve the interconnection signal transmission delay problem of traditional copper interconnection in small size application scenarios, and significantly improve the performance and reliability of the interconnection line;
[0028] 5. The Cu-Al alloy interconnection material prepared by the present application widens the potential window and slows down the hydrogen evolution side reaction by using a specific structure of aluminum salt and a "salt-in-water" solvation structure. Pulse plating regulation realizes copper-aluminum co-deposition, combined with annealing heat treatment, to obtain a uniform and dense plating layer. By precisely controlling the copper-aluminum atomic ratio, a nanoscale intermetallic compound dispersion structure is formed, reducing grain boundary defects and composition segregation, reducing electron transmission scattering loss, and inhibiting electromigration failure. The nanoscale uniform structure can minimize the effect of sub-micron interconnection line size;
[0029] 6. In the present application, water-based pulse plating does not require a vacuum environment, and the equipment is simple, which meets the needs of Damascene process trench filling, avoids the high vacuum energy consumption and complexity of magnetron sputtering, and increases the deposition rate by 50 times (up to 1-5 μm / min) compared with magnetron sputtering, reduces the equipment investment cost by 70%, directly adapts to 28 nm and below process wafer level interconnection manufacturing, significantly improves the industrialization efficiency and economy, and the aluminum content in the alloy can be continuously regulated between 5% and 20%.
[0030] The concept, specific structure and technical effects of the present application will be further described below with reference to the accompanying drawings, so as to fully understand the purpose, features and effects of the present application. BRIEF DESCRIPTION OF DRAWINGS
[0031] Figure 1 is the EDS surface scanning element distribution result of the copper-aluminum alloy plating layer prepared by pulse plating in Example 2 of the present application;
[0032] Figure 2is a grazing incidence XRD pattern of the copper-aluminum alloy plating layer prepared by galvanic plating and pulse plating respectively in Embodiment 1 and Embodiment 2 of the present application. DETAILED DESCRIPTION
[0033] The technical content of the present application will be more clearly understood and facilitated to be understood by introducing the preferred embodiments of the present application with reference to the accompanying drawings of the specification. The present application can be embodied in many different forms of embodiments, and the protection scope of the present application is not limited to the embodiments mentioned herein.
[0034] In the drawings, the components with the same structure are denoted by the same reference numerals, and the components with similar structure or function are denoted by similar reference numerals. The size and thickness of each component shown in the drawings are arbitrarily shown, and the present application is not limited to the size and thickness of each component. In order to make the drawing clearer, the thickness of some components is appropriately exaggerated in some places in the drawing.
[0035] The present application provides a preparation method of copper-aluminum alloy interconnection line by electroplating in aqueous solution system. The sample is subsequently subjected to annealing heat treatment, and the formation of alloy is promoted by promoting crystallization. The preparation method comprises the following steps:
[0036] Step 1, dissolve a certain amount of aluminum salt in deionized water and mix uniformly to obtain an aluminum salt solution.
[0037] Step 2, electroplating substrate pretreatment: paste insulating glue on the conductive cathode substrate, control the conductive area, then power on to remove oil, use dilute sulfuric acid pickling and deionized water rinsing treatment to obtain a clean conductive substrate after treatment.
[0038] Step 3, immerse the conductive substrate in the aluminum salt solution to activate the aluminum salt solution, and obtain the activated plating solution.
[0039] Step 4, add copper sulfate to the activated plating solution, mix and stir thoroughly to obtain a mixed plating solution containing copper ions and aluminum ions.
[0040] Step 5, immerse the pretreated conductive cathode substrate and metal anode material in the mixed plating solution for electroplating to obtain a copper-aluminum alloy plating layer.
[0041] Step 6, after electroplating, take out the sample and rinse the copper-aluminum alloy plating layer quickly with deionized water and blow dry, then remove the insulating glue, then rinse and blow dry the entire sample with deionized water to obtain a plating layer without surface contamination.
[0042] Step 7, annealing heat treatment operation is performed on the obtained copper-aluminum alloy plating layer to obtain a copper-aluminum alloy (Cu-Al alloy).
[0043] The aluminum salt in step 1 refers to aluminum salts with large volume of anions and strong electron delocalization, such as one or more of aluminum triflate (chemical formula Al(CF3SO3)3), aluminum bis(trifluoromethylsulfonylimide) (chemical formula Al[(CF3SO2)2N]3), aluminum bis(fluorosulfonylimide) (chemical formula Al[(FSO2)2N]3), aluminum trifluoroacetate (chemical formula Al(CF3COO)3), etc. The concentration of the aluminum salt is 0.2-5 M / L.
[0044] The concentration of the dilute sulfuric acid in step 2 is 1.54 mol / L.
[0045] The copper salt in step 4 is copper sulfate pentahydrate, and the concentration of the copper salt is 100-2000 ppm.
[0046] The electroplating in step 5 can be direct current electroplating, and the current density during electroplating is 1-6.25 A / dm2, the electroplating time is 3 min, and the stirring speed during electroplating is 500-1800 rpm.
[0047] The electroplating in step 5 can be pulse electroplating, and the average current density is 1-6.25 A / dm2, the pulse width is 0.2-1 s, the total electroplating time is 3-10 min, and the stirring speed during electroplating is 1000-2000 rpm.
[0048] The heating rate of the annealing heat treatment in step 7 is 5-20 ℃ / min; the temperature of the annealing heat treatment is 250-450 ℃; and the holding time of the annealing heat treatment is 1-3 h.
[0049] Example 1
[0050] A constant current electrodeposition method, i.e., direct current electroplating, is used to prepare the copper-aluminum alloy:
[0051] Aluminum triflate and copper sulfate pentahydrate are dissolved in deionized water in a certain proportion, and the plating solution is stirred to mix uniformly. Stainless steel is used as the electroplating substrate, the substrate is degreased and pickled to obtain a clean electroplating cathode, and appropriate electroplating parameters are selected for direct current electrodeposition to obtain a copper-aluminum composite coating on the surface of the substrate. Subsequent annealing heat treatment is required for the coating.
[0052] The concentration of aluminum triflate used in the plating solution is 0.2-5 M / L, and the concentration of copper sulfate is 200-2000 ppm. Constant current is used for deposition, the electrodeposition time is 3-20 min, the current density is 1-4 A / dm2, and the stirring speed is 1800 rpm.
[0053] The heating rate, annealing temperature, and holding time for annealing heat treatment need to be set. The heating rate is 5-20°C / min, the annealing temperature is 250-400°C, and the holding time is 1-2 hours. The purpose of annealing heat treatment is to promote the interdiffusion between atoms and promote the formation of alloys. High-temperature annealing also promotes the recrystallization and growth of the coating grains, effectively improving the conductivity of the coating.
[0054] The ratio of copper to aluminum alloy obtained by electroplating at different current densities varies. This is because the deposition potentials and diffusion rates of copper and aluminum ions in the plating solution are different, resulting in different electroplating efficiencies for copper and aluminum in the electrolyte. High current densities promote aluminum plating, while low current densities favor copper plating.
[0055] Example 2
[0056] Pulse electrodeposition method is used to prepare copper-aluminum alloy by pulse electroplating:
[0057] The electroplating process adopts pulse electroplating method, the average current density of pulse electroplating is set to 1-6.25A / dm2, the pulse width is 0.2-1s, and the total electroplating time is 3-10min. The obtained coating is also subjected to the above-mentioned annealing heat treatment.
[0058] The EDS surface scanning element distribution results of the copper-aluminum alloy coating prepared by pulse electroplating are as follows Figure 1 As shown in the figure, the use of pulse plating can better control the alloy composition and produce a coating with a higher aluminum content. The pulse current will cause periodic changes in the ion concentration on the electrode surface, which is beneficial to grain refinement. The fine and uniform grain structure can improve the density, flatness and corrosion resistance of the coating. By adjusting the pulse plating parameters, such as current, pulse width, plating cycle, etc., the deposition rate of different elements can be selectively controlled, which is beneficial to the preparation of alloy coatings with target composition. Figure 2 Figure 2 shows grazing-incidence XRD patterns of the copper-aluminum alloy coatings prepared by constant current electroplating and pulse electroplating, respectively, in Examples 1 and 2 of the present invention. The XRD patterns reveal that, under different electroplating methods and parameters, the coatings contain alloy phases such as Al2Cu and Cu9Al4. The Cu phase diffraction peak is relatively stronger in constant current electroplating, while the Al2Cu peak is prominent in pulse electroplating, indicating that the electroplating parameters affect the phase composition and diffraction intensity.
[0059] The present invention also provides a Cu-Al alloy interconnect material prepared according to the above method, which is used in semiconductor devices. The atomic ratio of Cu to Al in the copper-aluminum alloy coating is 0.1-10:1, and the specific ratio is controlled by the concentration of the aluminum salt in step 1 (0.2-5 M / L) and the concentration of copper sulfate in step 4 (100-2000 ppm).
[0060] Furthermore, the copper-aluminum alloy after annealing heat treatment forms a nanocrystalline structure with an average grain size of 50-200 nm, and the XRD spectrum shows the presence of alloy phases such as CuAl2 and Cu9Al4.
[0061] The preferred embodiments of the present invention have been described in detail above. It should be understood that numerous modifications and variations based on the concepts of the present invention are possible without inventive effort by those skilled in the art. Therefore, any technical solution that can be derived by one skilled in the art through logical analysis, reasoning, or limited experimentation based on the concepts of the present invention and the prior art should be within the scope of protection defined by the claims.
Claims
1. A method for preparing a Cu-Al alloy interconnect material, characterized in that: The following steps are involved: Step 1: dissolving a certain amount of aluminum salt in deionized water and mixing uniformly to obtain an aluminum salt solution; Step 2: Pre-treat the electroplating substrate by applying insulating glue to the conductive cathode substrate to control the conductive area, then conduct degreasing by electrification, pickling with dilute sulfuric acid and rinsing with deionized water to obtain a clean conductive substrate. Step 3, immersing the conductive substrate in an aluminum salt solution to activate the aluminum salt solution to obtain an activated plating solution; Step 4: adding copper salt to the activated plating solution, and thoroughly mixing and stirring to obtain a mixed plating solution containing copper ions and aluminum ions; Step 5: Immersing the pretreated conductive cathode substrate and the metal anode material in a mixed plating solution for electroplating to obtain a copper-aluminum alloy coating; Step 6: After the electroplating is completed, the sample is taken out and the copper-aluminum alloy coating is quickly rinsed and dried with deionized water. The insulating glue is then removed, and the entire sample is rinsed and dried with deionized water to obtain a coating without surface contamination. Step 7: performing an annealing heat treatment operation on the coating obtained in step 6 to obtain a copper-aluminum alloy.
2. The method for preparing a Cu-Al alloy interconnect material according to claim 1, wherein: The aluminum salt in step 1 includes one or more of aluminum trifluoromethanesulfonate, aluminum bistrifluoromethanesulfonyl imide, aluminum bisfluorosulfonyl imide, and aluminum trifluoroacetate, and the concentration of the aluminum salt is 0.2-5 M / L.
3. The method for preparing the Cu-Al alloy interconnect material according to claim 1, wherein: The concentration of the dilute sulfuric acid in step 2 is 1.54 mol / L.
4. The method for preparing a Cu-Al alloy interconnect material according to claim 1, wherein: The copper salt in step 4 is copper sulfate pentahydrate, and the concentration of the copper salt is 100-2000 ppm.
5. The method for preparing the Cu-Al alloy interconnect material according to claim 1, wherein: In step 5, the electroplating is direct current electroplating, and the current density during electroplating is 1-6.25A / dm 2 The electroplating time is 3-20min, and the stirring speed during electroplating is 500-1800rpm.
6. The method for preparing the Cu-Al alloy interconnect material according to claim 1, wherein: In step 5, the electroplating is pulse electroplating with an average current density of 1-6.25A / dm 2 , pulse width is 0.2-1s, total electroplating time is 3-10min, and stirring speed during electroplating is 1000-2000rpm.
7. The method for preparing the Cu-Al alloy interconnect material according to claim 1, wherein: The heating rate of the annealing heat treatment in step 7 is 5-20°C / min; the temperature of the annealing heat treatment is 250-450°C; and the holding time of the annealing heat treatment is 1-3h.
8. A Cu-Al alloy interconnect material prepared according to the method of any one of claims 1 to 7, characterized in that: The atomic ratio of Cu to Al in the copper-aluminum alloy coating is 0.1-10:
1.
9. The Cu-Al alloy interconnect material according to claim 8, wherein: After annealing heat treatment, the copper-aluminum alloy forms a nanocrystalline structure with an average grain size of 50-200 nm.
10. Use of the Cu-Al alloy interconnect material prepared by the preparation method according to any one of claims 1 to 7 in semiconductor devices.